PEMBERIAN DOSIS PUPUK N, P K, Mg SESUAI TARGET PRODUKSI DAN JARAK TANAM PADA TANAMAN SAWI (Brassica juncea L.) - Putri Datin Andriani Lubis (Institute of Computer Science (IOCS), 2021)
The objective of this research is to study the affect of dosage of N, P, K, Mg fertilizer based on the production target and spacing of mustard plant (Brassica juncea L.). This research was conducted in the Research and Technology Laboratory of the Faculty of Agriculture, University of North Sumatra, Laboratory of Agricultural Technology Assessment Center (BPTP) and at Pasar 1, Tanjung Sari, Medan Selayang subdistrict begining April until November 2019. This research used randomized complete block design (RCBD) with 2 treatments. The first is dosage of N, P, K, Mg fertilizer based on the production target with 4 levels, which are: 0 tons/ha, 15 tons/ha, 30 tons/ha and 45 tons/ha. The second is spacing with 3 levels, those are: 30 cm x 15 cm, 30 cm x 20 cm and 30 cm x 25 cm. The results of this study showed that the treatment of dosage of N, P, K and Mg fertilizer based on the production target significantly increased the height of mustard plant and number of leaves at the age of 3 WAP, yield of samples and plants per plot. The spacing treatment significantly increased the number of leaves at the age of 3 WAP. The interactions between the two treatments did not significantly effect all of the variables observed.